The stoichiometric divisome: a hypothesis - Egan, Alexander J. F.; Vollmer, Waldemar (Frontiers in Microbiology, 2015)
Dividing Escherichia coli cells simultaneously constrict the inner membrane, peptidoglycan layer and outer membrane to synthesize the new poles of the daughter cells. For this, more than 30 proteins localize to mid-cell where they form a large, ring-like assembly, the divisome, facilitating division. Although the precise function of most divisome proteins is unknown, it became apparent in recent years that dynamic protein-protein interactions are essential for divisome assembly and function. However, little is known about the nature of the interactions involved and the stoichiometry of the proteins within the divisome. A recent study (Li et al., 2014) used ribosome profiling to measure the absolute protein synthesis rates in E. coli. Interestingly, they observed that most proteins which participate in known multiprotein complexes are synthesized proportional to their stoichiometry. Based on this principle we present a hypothesis for the stoichiometry of the core of the divisome, taking into account known protein-protein interactions. From this hypothesis we infer a possible mechanism for PG synthesis during division.